GETTING TO GRIPS WITH THE LARGER PATTERNS IN THE REPORT TEXT - Syarah Nur Rahmah; Evie Kareviati (PROJECT (Professional Journal of English Education), 2019)
This research is aimed to know about what larger patterns are used in the report text and what is the role of larger patterns used for the reader. The researcher found that the report text about Australian senator hit with egg after blaming imigration for mosque attack (Karasz, 2019) used claim-counterclaim patterns.The role of claim-counterclaim patterns in that report text is to make readers easy to understand the text, as the reader will know who is the one who was claimed at the beginning as an anti-imigration person, and why he hit a teenager, and what is the reason the teenager smashed him. The researcher suggests for the futher researcher to use other more interesting sources to find more the larger patterns and to knowabout the role of the patterns.Keywords: Larger patterns, report text